2017
DOI: 10.1097/md.0000000000006619
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of digital single-operator cholangioscopy for diagnostic and therapeutic procedure (with videos)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(20 reference statements)
4
15
0
1
Order By: Relevance
“…Only a few digital SOC studies reported selective guidewire insertion in a limited number of patients (4-7 patients) with success rates of 57-75%. 7,10 Particularly in patients with complex strictures, the enhanced imaging quality of the digital SOC could help identify the ostium of the stricture and may prevent more invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few digital SOC studies reported selective guidewire insertion in a limited number of patients (4-7 patients) with success rates of 57-75%. 7,10 Particularly in patients with complex strictures, the enhanced imaging quality of the digital SOC could help identify the ostium of the stricture and may prevent more invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other digital SOC studies that report stone removal rates of 86-100%. 7,9,10 According to a meta-analysis including 244 cholangioscopies in patients with difficult stone disease, the success rate for fibre-optic SOC was 87%. 22 We conclude that compared with fibre-optic SOC, for complex stone disease, the improved digital imaging quality might not improve biliary stone clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low specificity of direct visualization alone implies pathologic analysis for definitive diagnosis [2]. Most studies reported an adequate quality sampling in 82–97% of biopsies obtained by CCS [6, 11, 12, 14] with a diagnostic accuracy, sensitivity, and specificity of 49–93%, 49–82%, and 97–98%, respectively [6, 10-12, 14, 15]. The diagnostic accuracy of biliary malignancy increases to 96% when combining cholangioscopic visualization and biopsy [9, 10, 12, 14].…”
mentioning
confidence: 99%
“…Regarding diagnosis of biliary lesions, brush cytology and standard forceps biopsy obtained by indirect visualization under fluoroscopic guidance of the biliary tract have a limited diagnostic accuracy (39–54%) with low sensitivity (6–51%) and specificity (55%) [2, 5, 6, 10, 11]. Recent systematic reviews and meta-analyses evaluated the diagnostic power of peroral cholangioscopy for malignant biliary stricture based on visual impression and CCS-guided biopsies, with a success rate of 90–100% [10, 12, 13].…”
mentioning
confidence: 99%